Extraction of spikes from brain signals - Anderson, Tommy (2012)
Meditation is a practice in which the practitioner trains to self-induce a state of peacefulness. It is practiced in different religions and cultures, mainly with the aim of spiritual growth. In modern days, meditation is widely practiced with secular meditation techniques, with the aim of relaxation of mind and reduction of stress.